THE USE OF TRIPHASIC HYALURONAN-CHITOSAN-STRONTIUM CHLORIDE MEMBRANE IN TREATING INTRABONY DEFECT "RANDOMIZED CLINICAL TRIAL" - Nema Khedr Sayed; Hala Hassan Yassin; Azza Ezz El-Arab; Norina Consuela Forna; Shereen Fathy Ahmed (Romanian Society of Oral Rehabilitation, 2024)
Background: The goal of periodontal treatment is to stop this progressive destruction by controlling infection, thus preventing tooth loss. The aim of this work was to evaluate the efficacy of the combined effect of Chitosan, hyaluronan, and strontium chloride membranes in the treatment of periodontal intrabony defect. Methods: This research was randomized controlled trial. This study was carried out on 36 patients with an age range between 25 and 55 years. The patients were divided into two equal groups as follows: Group A (Control group): patients were treated with open flap debridement and group B (Test group): patients were treated surgically with hyaluronan, chitosan, and strontium chloride membrane. Results: The pain was significantly reduced in group B compared to group A at D1 and D2 (P<0.001), while the remaining durations were insignificantly different between both groups. The gingival index and probing depth was significantly reduced after 3 months and after 6 months compared to baseline in group A and in group B (P<0.001). Conclusions: The use of triphasic Hyaluronan - Chitosan - Strontium Chloride membrane in conjunction with periodontal flap surgery in treating intrabony defect did not show a statistically significant difference in comparison to OFD alone. Regarding periodontal probing depth, clinical attachment loss, gingival index, and radiographic bone fill, there was an improvement in both groups. Moreover, tissue response to the triphasic Hyaluronan -Chitosan- Strontium Chloride membrane was favorable as reflected by reduced pain and swelling.